Conservation covenants for ecosystem restoration: adapting an old instrument to a new global conservation challenge? - Richardson, Benjamin J.; Brugler, Sarah; Fitzsimons, James A.; McCormack, Phillipa C.; Akhtar-Khavari, Afshin (Frontiers in Conservation Science, 2024)
Conservation covenants are an important legal tool for enabling private land conservation, whose significance has grown in light of new global commitments to expand areas of land and water protected and restored. Covenants’ traditional focus on conservation of existing natural values rather than restoration of degraded land or active management under a changing climate, pose significant challenges to its flexibility and efficacy. In Australia, recent national legal reforms to incentivise private land conservation, notably the Nature Repair Act 2023, will need to consider how to align reforms with conservation covenants that are regulated by different laws with different criteria and goals. Here we identify some pathways for enabling conservation covenants to play an expanded role in the context of ecosystem restoration and climate adaptation.